The sacred in modern western European music: Between fires of cultural paradigms - Liva, Natalia (Opción, 2020)
The article concerns identification and description of a number of phenomena, taking place in Western European music of the second half of the 20th – early 21st centuries and associated with a paradigm shift in the worldview via philosophical, culturological and musicological research methods. As a result, the authors find expression in the following musical and cultural phenomena: ambivalence of postmodern postulates, indicating not only breakdown of traditional cultural values but also the birth of new musical thinking. In conclusion, the processes given find bright expression in music both on the conceptual level and on more latent level of musical language.